2021
DOI: 10.1155/2021/2042114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Metabolism-Related Genes in Clear Cell Renal Cell Carcinoma

Abstract: Background. Clear cell renal cell carcinoma (ccRCC) is a cancer with abnormal metabolism. The purpose of this study was to investigate the effect of metabolism-related genes on the prognosis of ccRCC patients. Methods. The data of ccRCC patients were downloaded from the TCGA and the GEO databases and clustered using the nonnegative matrix factorization method. The limma software package was used to analyze differences in gene expression. A random forest model was used to screen for important genes. A novel Ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…S100A9 is an oxidative stress gene ( Saheb Sharif-Askari et al, 2021 ), and Lv et al (2020) found that S100A9 enhances prostate cancer cell invasion by activating TLR4/NF-κB/integrin β1/FAK signaling. Chen et al (2021) found that β-sarcoglycan ( SGCB ) is a prognostic metabolism-related gene in clear-cell RCC. Yu et al (2014) found that mutations in the inflammation-related gene TNFRSF1B might alter the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 is an oxidative stress gene ( Saheb Sharif-Askari et al, 2021 ), and Lv et al (2020) found that S100A9 enhances prostate cancer cell invasion by activating TLR4/NF-κB/integrin β1/FAK signaling. Chen et al (2021) found that β-sarcoglycan ( SGCB ) is a prognostic metabolism-related gene in clear-cell RCC. Yu et al (2014) found that mutations in the inflammation-related gene TNFRSF1B might alter the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to previous work, Chen et al (2021) performed a series of analyses based on metabolic genes in ccRCC, but metabolic alterations encompass multiple pathways. We performed studies in individual pathways (fatty acid metabolic pathway).…”
Section: Discussionmentioning
confidence: 99%
“…The NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, 4like 2 can be used as an invasive marker (99-101). Applying bioinformatics technology to tumor studies has even shown explosive growth in recent years (102)(103)(104)(105). Mining the cancer genome atlas and gene expression omnibus database has made it possible to obtain many differentially expressed molecular indicators that affect patient survival without much effort.…”
Section: Potential Molecular Targetsmentioning
confidence: 99%